2017
DOI: 10.1039/c7cc06541h
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-based reduction of nitrate to nitric oxide utilizing a proton-responsive secondary coordination sphere

Abstract: Utilizing the proton-responsive pyridinediimine ligand [(2,6-PrCH)(N[double bond, length as m-dash]CMe)(N(Pr)CH)(N[double bond, length as m-dash]CMe)CHN] (didpa), the ligand-based reduction of nitrate (NO) to nitric oxide (NO) was achieved. The bioinspired [Fe(Hdidpa)(CO)] was shown to react with tetrabutylammonium nitrate to form the dinitrosyl iron complex [Fe(didpa)(NO)]. The didpa scaffold was shown to provide two electrons for the net reduction of NO to NO in 43% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Similar to the previously reported Fe(didpa)(CO) 2 (didpa = [(2,6- i PrC 6 H 3 )(N=CMe)(N( 1 Pr) 2 C 2 H 4 )(N=CMe)C 5 H 3 N]) complex, 50 3 and 4 both react with two equivalents NO 2 − and four equivalents H + (Scheme 1, middle) yielding the representative dinitrosyl iron complexes (DNICs), [Fe( Pyrr PDI)(NO) 2 ] + ( 5 ) and [Fe( Mor PDI)(NO) 2 ] + ( 6 ). The solid state structures of 5 and 6 are shown in Figure 2.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the previously reported Fe(didpa)(CO) 2 (didpa = [(2,6- i PrC 6 H 3 )(N=CMe)(N( 1 Pr) 2 C 2 H 4 )(N=CMe)C 5 H 3 N]) complex, 50 3 and 4 both react with two equivalents NO 2 − and four equivalents H + (Scheme 1, middle) yielding the representative dinitrosyl iron complexes (DNICs), [Fe( Pyrr PDI)(NO) 2 ] + ( 5 ) and [Fe( Mor PDI)(NO) 2 ] + ( 6 ). The solid state structures of 5 and 6 are shown in Figure 2.…”
Section: Resultssupporting
confidence: 90%
“…4147 Our group has been active in developing methodologies that control the movement of both protons and electrons for biologically relevant reactions by utilizing the redox-active pyridinediimine (PDI) scaffold merged with a proton-responsive secondary coordination sphere. 4850 Those preliminary studies successfully showed: 1) the PDI scaffold can be tailored to facilitate NO 2 − reduction, and; 2) the NO 2 − reduction is dependent on the protonation state of the secondary coordination sphere (proton-responsivity). Furthermore, given the revelations of the role ligand hemilability plays in biomimicry, 5153 we reasoned that the pendant base(s) could be utilized to introduce hemilability into the PDI, yielding ligand scaffolds that increase activity even further.…”
Section: Introductionmentioning
confidence: 99%
“…However there are few examples of molecular electrocatalysts for nitrate reduction, 25 29 and very little is known about their reaction mechanisms. While a number of examples of stoichiometric conversions of nitrate by homogeneous metal complexes suggest the importance of hydrogen donor functionalities for nitrate activation, 30 , 31 these results do not provide guidelines for designing electrocatalysts that are selective for nitrate reduction.…”
Section: Introductionmentioning
confidence: 94%
“…These integrated (yet uncoupled) complexes are capable of storing both protons and electrons for transfer to substrate. 71,72…”
Section: Introductionmentioning
confidence: 99%